Pengaruh Social Media Marketing dan Brand Ambassador Terhadap Keputusan Pembelian Produk POND’S (Studi Pada Pengguna Produk POND’S di Kabupaten Banyumas) - Devi Shifa Kamila; Sari Listyorini; Andi Wijayanto (Jurnal Ilmu Administrasi Bisnis, 2024)
Cosmetics are a primary need for women. Pond's is a beauty product that has been around since 1846 and has become an international product in the field of skin care. High demand encourages increasingly tight competition between companies. Companies must implement the right strategies to increase sales, such as utilizing social media marketing and brand ambassadors to expand market reach and encourage purchasing decisions. This research aims to determine the influence of social media marketing and brand ambassadors on POND'S purchasing decisions in Banyumas Regency. The type of research used is explanatory research with a sample size of 100 respondents who are Pond's users in Banyumas. The sampling technique uses non-probability sampling with purposive sampling and accidental sampling methods. Data analysis for this research uses SPSS 26. The research results show that social media marketing has significant positive influence on purchasing decisions for Pond's products in Banyumas. Brand ambassadors also have a significant positive influence on purchasing decisions for Pond's products in Banyumas. In this research, it was also found that social media marketing and brand ambassadors had a simultaneous influence on the decision to purchase Pond's products in BanyumasKeywords: Social Media Marketing; Brand Ambassador; Purchase DecisionKosmetik merupakan kebutuhan primer bagi wanita. Pond's adalah produk kecantikan yang ada sejak tahun 1846 dan menjadi produk internasional dalam bidang perawatan kulit. Permintaan yang tinggi mendorong persaingan antar perusahaan yang semakin ketat. Perusahaan harus menerapkan strategi yang tepat untuk meningkatkan penjulan seperti memanfaatkan social media marketing dan brand ambassador untuk memperluas jangkauan pasar dan mendorong keputusan pembelian. Penelitian ini bertujuan untuk mengetahui pengaruh social media marketing dan brand ambassador terhadap keputusan pembelian POND’S di Kabupaten Banyumas. Tipe penelitian yang digunakan adalah explanatory research dengan jumlah sampel 100 responden yang merupakan pengguna Pond's di Banyumas. Teknik pengambilan sampel menggunakan non-probability sampling dengan metode purposive sampling dan accidental sampling. Analisis data penelitian ini menggunakan SPSS 26. Hasil penelitian menunjukan social media marketing memiliki pengaruh positif signifikan terhadap keputusan pembelian produk Pond's di Banyumas. Brand ambassador juga memiliki pengaruh positif signifikan terhadap keputusan pembelian produk Pond's di Banyumas. Dalam penelitian ini juga ditemukan bahwa social media marketing dan brand ambassador memiliki pengaruh secara simultan terhadap keputusan pembelian produk Pond's di Kabupaten Banyumas.Kata Kunci: Social Media Marketing; Brand Ambassador; Keputusan Pembelian